Second-Generation Women Entrepreneurs in Chinese Family-Owned Businesses: Motivations, Challenges, and Opportunities. Issue 2 (May 2020) - Li, Jessica; Sun, Judy Yi; Wang, Lianjuan; Ke, Jie
The Problem: Family-owned businesses provide a large portion of the job opportunities in the Chinese economy. Many successful family-owned businesses in China were established during the initial years of economic reform in the late 1970s and 1980s. Today, as the founders of these companies approach retirement, leadership transition is becoming a pressing issue. Among the various factors involved in family business succession are gender-specific obstacles faced by women who seek to achieve leadership positions. Women entrepreneurs in China are gradually increasing in number, but those who desire to take the helm of family-owned companies face important social and structural challenges in China's male-dominated business culture. The Solution: In this study, we used a qualitative interview approach to learn about the experiences of second-generation women entrepreneurs in Chinese family-owned businesses and to better understand their motivations along with the challenges and opportunities that they face. The findings revealed that the motivations of these women entrepreneurs were centered more on internal "pull" factors (e.g., self-actualization) rather than external "push" factors (e.g., economic pressures). The major challenges that were reported included tense relationships with parents, gender-role conflicts, and alignment issues in relation to their family businesses' established culture. Understanding these factors can help in identifying opportunities for effective human resource development and promoting women's entrepreneurship in the Chinese context. The Stakeholders: Second-generation women entrepreneurs, family businesses in China, women leaders, and human resource development professionals.